Best Practices for Biostatistical Consultation and Collaboration in Academic Health Centers. Issue 2 (2nd April 2016) - Perkins, Susan M.; Bacchetti, Peter; Davey, Cynthia S.; Lindsell, Christopher J.; Mazumdar, Madhu; Oster, Robert A.; Peduzzi, Peter N.; Rocke, David M.; Rudser, Kyle D.; Kim, Mimi
ABSTRACT: Given the increasing level and scope of biostatistics expertise needed at academic health centers today, we developed best practices guidelines for biostatistics units to be more effective in providing biostatistical support to their institutions, and in fostering an environment in which unit members can thrive professionally. Our recommendations focus on the key areas of: (1) funding sources and mechanisms; (2) providing and prioritizing access to biostatistical resources; and (3) interacting with investigators. We recommend that the leadership of biostatistics units negotiate for sufficient long-term infrastructure support to ensure stability and continuity of funding for personnel, align project budgets closely with actual level of biostatistical effort, devise and consistently apply strategies for prioritizing and tracking effort on studies, and clearly stipulate with investigators prior to project initiation policies regarding funding, lead time, and authorship.